2023
DOI: 10.1128/spectrum.05320-22
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition Disrupts Cecal Microbiota and Epithelium Interactions, Epithelial Metabolism, and Immune Responses in a Pregnant Sheep Model

Abstract: Undernutrition is commonly encountered in ruminant production, especially during pregnancy and lactation in females. Undernutrition not only induces metabolic diseases and threatens pregnant mothers’ health, but also inhibits fetal growth and development, leading to weakness or even death of fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In a study involving sheep, it was observed that malnutrition adversely affected cecal microbial diversity, composition, and fermentation parameters. This, in turn, impeded intestinal immunological functions and hindered epithelial renewal [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving sheep, it was observed that malnutrition adversely affected cecal microbial diversity, composition, and fermentation parameters. This, in turn, impeded intestinal immunological functions and hindered epithelial renewal [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, G-protein-coupled receptor activity plays a crucial role in maintaining cell proliferation and migration [43], especially in the intestine, where leucinerich repeat-containing G-protein-coupled receptor 5+ (LGR5+) stem cells can promote intestinal epithelial renewal. The cytokine-cytokine receptor pathway can participate in the maintenance of barrier function [44,45]. Aon et al found that glycine-serine-threonine metabolism can also cooperate with other signaling pathways to enhance cell activity [46].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of ammonia nitrogen (NH 3 -N) was determined using a spectrophotometer (UV5, METTLER TOLEDO Technology Co., Shanghai, China) following the method described by Feng et al [ 23 ]. The Comas Brilliant Blue method was utilized to measure the microbial protein (MCP) content of the rumen fluid samples [ 24 ]. The volatile fatty acids (VFAs) contents in the rumen fluid were measured using gas chromatography equipped with a capillary column of 30.00 m × 0.32 mm × 0.50 µm.…”
Section: Methodsmentioning
confidence: 99%
“…The volatile fatty acids (VFAs) contents in the rumen fluid were measured using gas chromatography equipped with a capillary column of 30.00 m × 0.32 mm × 0.50 µm. The detector’s hydrogen pressure and air pressure were set to 0.40 MPa, while the capillary column pressure was set to 0.60–0.80 MPa [ 24 ].…”
Section: Methodsmentioning
confidence: 99%